Evaluation of the properties on carrageenan bio-films with Chlorella vulgaris blending - N. H., Mat Yasin; N. A., Othman; F., Adam (Taylor & Francis, 2022)
Microalgae are multicellular species that exist individually or in groups which typically found in freshwater and marine systems and a good and highly potential source to produce bio-films. Bio-films with carrageenan possessed several drawbacks that needed to be encountered. The purpose of this study is to observe the number of microalgae cell influenced the performance of the bio-film obtained. Cultivation of free cell C. vulgaris microalgae was conducted in Bold’s Basal Medium (BBM) for 16 days. Growth curve of the C. vulgaris, lipid extraction and FAMES determination was conducted on the alternate days of cultivation. 3 mL of C. vulgaris microalgae was added into the formulation of carrageenan at the alternate days of cultivation (D-0, 4, 8, 12, and 16). Results shows, the number of cell, percentage oil yield and FAMEs amount of C. vulgaris at D-16 is the highest which 1.19 × 1010 cell/mL, 27.74% and 17.76 mg/g, respectively. Hence affect the tensile strength of the bio-film and the solution viscosity with 36.26 Mpa and 245.29 mpa/s, respectively. It also shows the lowest value of moisture content which increases the EAB of the biofilm with 10.99% moisture and 50.24% elasticity. With the high number of cell shows the film has the highest value of water contact angle with 107.11°. It also requires the highest activation energy (42.16 kJ/mol) to decompose (80.63%). This can be concluded that the higher the number of cell and percentage oil yield with high amount of FAMEs, the better surface hydrophobicity of the bio-films obtained.